2015
DOI: 10.1002/cphc.201500299
|View full text |Cite
|
Sign up to set email alerts
|

Length‐Scale‐Dependent Phase Transformation of LiFePO4: An In situ and Operando Study Using Micro‐Raman Spectroscopy and XRD

Abstract: The charge and discharge of lithium ion batteries are often accompanied by electrochemically driven phase-transformation processes. In this work, two in situ and operando methods, that is, micro-Raman spectroscopy and X-ray diffraction (XRD), have been combined to study the phase-transformation process in LiFePO4 at two distinct length scales, namely, particle-level scale (∼1 μm) and macroscopic scale (∼several cm). In situ Raman studies revealed a discrete mode of phase transformation at the particle level. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Several models, such as Shrinking core model (Padhi et al, 1997), Domino cascade model (Delmas et al, 2008) describe the phase transformation between LiFePO 4 and FePO 4 , but the mechanism is still in debate. As a result, several operando techniques were applied to understand the process (Perea et al, 2012;Orikasa et al, 2013;Ouvrard et al, 2013;Dong et al, 2017), especially using operando XRD (Shin et al, 2008;Roberts et al, 2014) and operando Raman Siddique et al, 2015). The LFP↔FP transition is generally considered as a two-phase reaction (Chen et al, 2006;Laffont et al, 2006;Zhu Y. et al, 2013), also confirmed by XRD measurements conducted on slow cycled cells (Andersson et al, 2000;Shin et al, 2011;Siddique et al, 2015).…”
Section: Lifepomentioning
confidence: 99%
See 1 more Smart Citation
“…Several models, such as Shrinking core model (Padhi et al, 1997), Domino cascade model (Delmas et al, 2008) describe the phase transformation between LiFePO 4 and FePO 4 , but the mechanism is still in debate. As a result, several operando techniques were applied to understand the process (Perea et al, 2012;Orikasa et al, 2013;Ouvrard et al, 2013;Dong et al, 2017), especially using operando XRD (Shin et al, 2008;Roberts et al, 2014) and operando Raman Siddique et al, 2015). The LFP↔FP transition is generally considered as a two-phase reaction (Chen et al, 2006;Laffont et al, 2006;Zhu Y. et al, 2013), also confirmed by XRD measurements conducted on slow cycled cells (Andersson et al, 2000;Shin et al, 2011;Siddique et al, 2015).…”
Section: Lifepomentioning
confidence: 99%
“…(B2) diffraction patterns from first two cycles stacked against the voltage profile; black vertical lines mark the positions of LFP peaks at the start of reaction; red vertical lines mark the position of FP peaks formed during the first cycle; with permission from AAAS. (C) Raman spectra collected on LFP electrode surface at a cycling rate of 0.3C (Siddique et al, 2015); (C1) carbon-rich spot A during charge; (C2) spot A during discharge; (C3) carbon-poor spot B during charge; (C4) spot B during discharge; (C5) corresponding electrochemical cell performance curve with vertical lines indicating the moment when the Raman spectra were taken; with permission from Wiley-VCH Verlag GmbH&Co. KGaA, Weinheim.…”
Section: Lifepomentioning
confidence: 99%
“…in real time. In the past few years, many researchers have tried to monitor in real time reactions inside batteries during electrochemical performance by using XRD [1,2,3,4], XAS [5,6,7], Raman [8,9,10,11,12,13,14,15,16,17], NMR [18], and so forth [19,20]. However, the studies for electrochemical reactions during the initial cycle is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, C. Delmas et al reported another phase transition mechanism, which is named the ‘domino-cascade’ model [31]. They assume that phase transformations at particle-level are fast, and small particles appear either fully charged (FePO 4 phase) or discharged (LiFePO 4 phase) due to a very rapid two-phase front [4,31]. The phase transition mechanism of LiFePO 4 has been also investigated through in situ Raman spectroscopy [4,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation